Recent perpectives into biochemisty of decavanadate - Aureliano, M. (2012)
The number of papers about decavanadate has doubled in the past decade. In the present review, new insights into decavanadate biochemistry, cell biology, and antidiabetic and antitumor activities are described. Decameric vanadate species (V10) clearly differs from monomeric vanadate (V1), and affects differently calcium pumps, and structure and function of myosin and actin. Only decavanadate inhibits calcium accumulation by calcium pump ATPase, and strongly inhibits actomyosin ATPase activity (IC50 = 1.4 μmol/L, V10), whereas no such effects are detected with V1 up to 150 μmol/L; prevents actin polymerization (IC50 of 68 μmol/L, whereas no effects detected with up to 2 mmol/L V1); and interacts with actin in a way that induces cysteine oxidation and vanadate reduction to vanadyl. Moreover, in vivo decavanadate toxicity studies have revealed that acute exposure to polyoxovanadate induces different changes in antioxidant enzymes and oxidative stress parameters, in comparison with vanadate. In vitro studies have clearly demonstrated that mitochondrial oxygen consumption is strongly affected by decavanadate (IC50, 0.1 μmol/L); perhaps the most relevant biological effect. Finally, decavanadate (100 μmol/L) increases rat adipocyte glucose accumulation more potently than several vanadium complexes. Preliminary studies suggest that decavanadate does not have similar effects in human adipocytes. Although decavanadate can be a useful biochemical tool, further studies must be carried out before it can be confirmed that decavanadate and its complexes can be used as anticancer or antidiabetic agents.